Plague and tularemia surveillance in hormozgan province, Southern Iran - Hossein Ahangari Cohan; Saber Esmaeili; Ahmad Mahmoudi; Ahmad Ghasemi; Amir Hesam Nemati; Mohammad Mehdi Gooya; Abdoljabbar Zakeri; Ehsan Mostafavi (BMC Veterinary Research)
Abstract Background Plague and tularemia are endemic rodent-borne zoonoses in Iran. This study investigated their presence of these diseases in wildlife populations in southern Iran. Sheepdogs were also surveyed as sentinel animals to provide early warning of potential outbreaks. Methods In August 2018, sampling involved the capturing rodents and collecting blood from wild carnivores and sheepdogs. Rodent spleen tissues and ectoparasites were analyzed using real-time PCR to detect Yersinia pestis (targeting the yihN, pla, and caf1 genes) and Francisella tularensis (targeting the ISFtu2 and fopA genes). All tissue samples underwent bacterial isolation. Additionally, rodents, wild carnivores, and sheepdogs were screened for specific antibodies to assess pathogen exposure. Results A total of 65 rodents were captured, primarily Rattus rattus (35.38%), Tatera indica (29.23%), and Acomys dimidiatus (20%). Serological surveys included 35 domestic sheepdogs (Canis lupus familiaris), 4 jackals (Canis aureus), and 3 Indian grey mongooses (Urva edwardsi). Thirty fleas, all of the genus Xenopsylla, were collected as ectoparasites. All samples tested negative for tularemia via agglutination assay. No wild mammals showed seropositivity, but plague-specific antibodies were detected in 4 sheepdogs (11.42%). Molecular tests and bacterial cultures for both plague and tularemia were negative. Conclusion The presence of plague-specific antibodies in sheepdogs suggest possible plague circulation in southern Iran, indicating a potential risk of human exposure.